Phosphotyrosine-Protein-Phosphatase and Diabetic Disorders. Further Studies on the Relationship between Low Molecular Weight Acid Phosphatase Genotype and Degree of Glycemic Control. Issue 2 (17th June 2013) - Lucarini, N.; Antonacci, E.; Bottini, N.; Borgiani, P.; Faggioni, G.; Gloria-Bottini, F.
Abstract : We have studied a new sample of 276 NIDDM patients from the population of Penne (Italy). Comparison of the new data with those of 214 diabetic pregnant women from the population of Rome reported in a previous paper has shown that the pattern of association between low molecular weight acid phosphatase genotype and degree of glycemic control is similar in the two classes of diabetic patients. Among nonobese subjects the proportion of ACP1*A (the allele showing the lowest enzymatic activity) is lower in diabetic patients with high glycemic levels (mean value greater than 8.9 mmol/l) than in diabetic patients with a low glycemic level (mean value less than 8.9 mmol/l). Among obese subjects no significant association is observed between glycemic levels and ACP1. Among nonobese subjects the concentration of f isoform of ACP1 is higher in patients showing a high glycemic level than in patients showing a low glycemic level. No significant difference is observed for s isoform.